Leveraging the digital economy for enhanced digital service trade exports: Lessons from China - Xiaoqing Ma; Yunke Huo; Tingting Zhu (PLoS ONE, 2025)
This study explores the transformative role of digital economy development on digital service trade exports, using China as a case study, to elucidate trends and lessons that may be applicable to other nations seeking to leverage digital advancements for economic growth in an increasingly interconnected global market. Analyzing panel data from 105 global economies between 2013 and 2021 with a trade gravity model, supplemented by robustness and heterogeneity tests, we demonstrate that the development level of the digital economy in trading nations significantly enhances China’s digital service trade exports, particularly impacting middle- and high-income countries. The sectors most affected include intellectual property and cultural services. Our findings reveal a notable positive correlation between digital economy indices and digital service export volumes, suggesting that advancements in digital infrastructure, market dynamics, and governance in partner countries facilitate this increase. Geographical distance and economic systems also play crucial roles, influencing trade costs and compatibility, respectively. These insights guide targeted policy recommendations to enhance digital service trade, emphasizing the need for strategic international cooperation and infrastructure investment to harness digital globalization’s full potential.